Track 2 - Del Valle, Vivien Marie Fontz 1997- (2017)
"This film centers on finding one's identity and the assurance of security in one's identity. It is drawn from the psychoanalytical theory of Jacques Lacan in which he suggests the Imaginary Order wherein an individual does not realize that s/he is his/her own person and not just a part of the world. Lacan's psychoanalytical theory suggests the Mirror stage as the point when one realizes its own individuality and identity, which is what the main character experienced by the end of the film. The film follows Tinig, a musician aspiring fame to continue her late father's one-hit music career. She struggles with rejection from music labels, with the pressure of continuing her father's dream, and with the pressure of seeing her friends more successful in her dream. The climax is reached when, in the midst of all the pressures, she hears her father's hit song and is reminded of his unconditional love for her in spite of her failures. This assurance helps her to continue making music, not for fame, but as an expression of herself no matter what the world expects of her. It aims to be an encouragement to the artists and creators who feel like they aren't good enough for the field that they are in. The film aims to be a reminder for individuals to continue on with their passions despite disappointments and failures because it is possible to encounter unconditional acceptance that will welcome both successes and failures with open arms."